A compact model for the zigzag triboelectric nanogenerator energy harvester. (6th September 2020) - Refaei, Akram; Seleem, Mohamed; Tharwat, Abdelrahman; Mostafa, Hassan
Summary: Energy is a global demand nowadays. Researchers and Scientists are trying every day to find new resources to generate energy. Mechanical energy is considered one of the most essential energy resources in the world. It can be easily generated and transferred into electrical energy. There are a lot of new technologies that are working to develop small and portable energy harvesters for electronic devices such as piezoelectric and triboelectric nanogenerators (TENGs). However, TENGs are more favorable to piezoelectric nanogenerators due to the availability of nontoxic materials. Moreover, they are cheap and exhibit high performance. This article investigates one of the TENG devices, Zigzag structure. It presents an analytical derivation for the model that addresses all aspects of the TENG such as the output voltage, the output current, the capacitance, the resistive load, the capacitive load and the harvested power step by step. The analytical derivation is also verified using COMSOL simulations to validate the results. The mismatch between the analytical derivation and COMSOL is 0.022% in the open circuit voltage and 0.33% in short circuit charge. Electrical behavior is presented afterwards using Verilog‐A in Cadence to examine the performance of the TENG devices in real life situations. For the chosen parameters, the device delivers a maximum voltage of 23 KV at nearly 90 ° and a maximum current of 7.5 μA at nearly 10°. The maximum reported output power for a load of 5 GΩ is 5.2 mW.